Improving generative inverse design of molecular catalysts in small data regime - François Cornet; Pratham Deshmukh; Bardi Benediktsson; Mikkel N Schmidt; Arghya Bhowmik (Machine Learning: Science and Technology)
Deep generative models are a powerful tool for exploring the chemical space within inverse-design workflows; however, their effectiveness relies on sufficient training data and effective mechanisms for guiding the model to optimize specific properties. We demonstrate that designing an expert-informed data representation and training procedure allows leveraging data augmentation while maintaining the required sampling controllability. We focus our discussion on a specific class of compounds (transition metal complexes), and a popular class of generative models (equivariant diffusion models), although we envision that the approach could be extended to other chemical spaces and model types. Through experiments, we demonstrate that augmenting the training database with generic but related unlabeled data enables a practical level of performance to be reached.